2000
DOI: 10.1063/1.1318731
|View full text |Cite
|
Sign up to set email alerts
|

Faceted inversion domain boundary in GaN films doped with Mg

Abstract: Homoepitaxial GaN films doped with Mg were grown by rf-plasma molecular beam epitaxy on Ga-polarity (0001) MOCVD templates. Convergent beam electron diffraction analysis establishes that the film polarity changes from [0001] to [0001] when the Mg flux during growth is approximately one monolayer per second. Secondary ion mass spectrometry indicates a doping concentration of ~10 20 cm-3 in the film where the inversion occurs and shows a reduced Mg incorporation efficiency after further growth. Transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
94
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 7 publications
20
94
2
Order By: Relevance
“…20 Thus, these results demonstrate that under identical growth conditions, net Mg acceptor incorporation is more efficient for Ga-face compared to N-face material. This observation is consistent with prior reports that Mg doping of GaN results in greater total Mg incorporation 8 and higher p-type conductivity 21 for material grown with Ga-face polarity compared to N-face material and suggests that avoidance of inversion domain formation is essential for optimization of p-type conductivity in GaN. In addition to revealing higher net Mg acceptor incorporation into Ga-face compared to N-face material, SCM imaging indicates that higher net concentrations of ionized Mg acceptors can occasionally be present in the immediate vicinity of inversion domain boundaries than in the surrounding Ga-face and N-face materials.…”
Section: ͑3͒supporting
confidence: 82%
See 1 more Smart Citation
“…20 Thus, these results demonstrate that under identical growth conditions, net Mg acceptor incorporation is more efficient for Ga-face compared to N-face material. This observation is consistent with prior reports that Mg doping of GaN results in greater total Mg incorporation 8 and higher p-type conductivity 21 for material grown with Ga-face polarity compared to N-face material and suggests that avoidance of inversion domain formation is essential for optimization of p-type conductivity in GaN. In addition to revealing higher net Mg acceptor incorporation into Ga-face compared to N-face material, SCM imaging indicates that higher net concentrations of ionized Mg acceptors can occasionally be present in the immediate vicinity of inversion domain boundaries than in the surrounding Ga-face and N-face materials.…”
Section: ͑3͒supporting
confidence: 82%
“…Because the p-type GaN films were grown under conditions leading to the presence of both Ga-polar and N-polar materials, a direct assessment of net Mg acceptor incorporation under identical growth conditions and its dependence on crystal polarity is possible. In addition, possible variations in net Mg acceptor incorporation in the vicinity of inversion domain boundaries, which have been proposed to contain increased concentrations of Mg in p-type GaN, 8,9 can be detected. Our results indicate that net Mg acceptor incorporation varies significantly with crystal polarity, being more efficient for Ga-polar than for N-polar material.…”
Section: Introductionmentioning
confidence: 99%
“…According to calculations by Northrup [19] our model would be energetically less favorable, but Mg could be 4-fold coordinated surrounded by 6-coordinated N and it would include change of stacking sequence from ab to bc and a shift on the pyramid side of 0.6 ±0.2Å between Ga sublattices in the matrix and the defect. Romano [20] suggested that the Ga sublattice continues across the pyramid side and Leroux [21] considered that the N sublattice continues across the same boundary, as similarly proposed by Northrup [19]. We believe that only our method gives enough resolution to see particular sublattices which was not presented by any other author up to now.…”
Section: Models and Results Discussionmentioning
confidence: 80%
“…This could limit further development of GaN based devices. Further increase of the Mg concentration, up to 1x10 20 cm -3 leads to a decrease of the free hole concentration. This is commonly interpreted as auto-compensation due to increased formation of N vacancies or vacancy complexes with Mg [1].…”
Section: Introductionmentioning
confidence: 99%
“…A com pa ri son of the exp eri menta l and sim ula ted CBED pa tterns di rectl y i ndi cates tha t the p ol ari ty of ZnO Ùlm wi th O-pl asm a pre-exposure is of O-p ol ar and tha t of ZnO Ùlm wi th Zn pre-exp osure i s of Zn-pol ar, whi ch i ndi cates tha t we ha ve contro l l ed pol ari ti es of wurtzi te crysta l by engi neeri ng the i nterf aces. W e wo ul d l i ke to stress agai n tha t the present results sugg est a general i zed m etho d to contro l the l atti ce p ol ari ty of Ùlm s by i nserti ng an i nterf ace l ayer wi th a center of sym m etry , thereby the conversi on of l atti ce p ol ari ty b ecomes p ossibl e. It shoul d b e noted tha t the pro posed metho d for contro l l i ng l atti ce p ol ari ty i s m ore general tha n any of the previ ous metho ds using i nverted do m ains [16,17 ].…”
Section: Pol Ar I Ty Cont R Ol L Ed Zno ùLms On Ga-pol Ar Gan Templ Atesmentioning
confidence: 99%